Terrestrial ecotoxicity of glyphosate, its formulations, and co-formulants: evidence from 2010–2023 - Szandra Klátyik; Gergely Simon; Marianna Oláh; Robin Mesnage; Michael N. Antoniou; Johann G. Zaller; András Székács (Environmental Sciences Europe, 2023)
Abstract Glyphosate (GLY), the most widely used herbicide in the world, is frequently detected in various environmental matrices, including soil, the foundation of agriculture. In practice, more than 2000 GLY-based herbicide (GBH) products are used, consisting of one or more active ingredients (AIs) and so-called “inert” co-formulants that increase the efficacy of the AIs. However, the focus of ecotoxicological assessments is mainly on AIs, while organisms are exposed to complex pesticide formulations under real-world conditions. Overall, the effects on non-target organisms indicate a broad range of biochemical and physiological modes of action, which contrasts with the general assumption that herbicides are specific and act only on target plants. Both GLY alone and GBHs have unintended side-effects on many terrestrial organisms, including non-target plants, microorganisms, insects, spiders, or earthworms, as well as vertebrates such as amphibians, reptiles, or mammals. One of the triggering mechanisms for these effects is oxidative stress with consequences on biochemical parameters and DNA damage. In addition, disruptions of various physiological, behavioral and ecological processes have been reported. Most studies have examined the short-term effects of a single application of GLY/GBH to a single species. However, the agricultural practice of applying GBHs two to three times during a cultivation season over an extended period of time, the interactions with other pesticides and agrochemicals applied to the same field, and effects on ecological interactions within the field and landscape are rarely considered. In the vast majority of cases, the toxicity of GBHs exceeds the toxicity of GLY, demonstrating that supposedly inert co-formulants are either toxic in their own right or interact and add to the toxicity of AIs. The chemical diversity of different GBHs and the non-disclosure of the co-formulants make it difficult to attribute effects to specific chemical substances within a GBH. Moreover, impurities in GBHs (e.g., heavy metals such as arsenic, chromium, cobalt) pose additional environment and food safety risks. These impacts are even more critical because GBHs are so widely distributed worldwide and interact with other pollutants and environmental stressors. Based on the available literature on terrestrial ecotoxicity, and given the drastic decline in biodiversity, we conclude that the continued high use of GBHs, resulting in increased exposure and risk, cannot be considered ecologically sustainable.